2005
DOI: 10.1007/s00787-005-0496-1
|View full text |Cite
|
Sign up to set email alerts
|

School factors and the emergence of depressive symptoms among young Norwegian adolescents

Abstract: The aims of this study were to examine correlates of self-reported depressive symptoms within the school area, and possible predictors of change in depressive symptom levels over a 1-year period in a large representative sample of 12 to 15-year-old adolescents in central Norway. The school variables were: school stress, class wellbeing, teacher support, and grades. Possible confounding factors were age, SES, ethnicity, and parental divorce. We also examined the strengths of these relationships. In the cross-se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
93
2
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(104 citation statements)
references
References 34 publications
8
93
2
1
Order By: Relevance
“…Given the cross sectional design, conclusions on directions of causality are not possible. However, longitudinal studies of self-efficacy [8], low teacher support [11], and bullying [32] have showed an increased risk for depressive symptoms. Because the data were self-reported, the accuracy of the results depends solely on respondents' subjective assessments.…”
Section: Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the cross sectional design, conclusions on directions of causality are not possible. However, longitudinal studies of self-efficacy [8], low teacher support [11], and bullying [32] have showed an increased risk for depressive symptoms. Because the data were self-reported, the accuracy of the results depends solely on respondents' subjective assessments.…”
Section: Limitationsmentioning
confidence: 99%
“…However, previous findings on the effects of low self-esteem and low self-efficacy are inconsistent, and in studies where effects have been found, they have been small [9]. Psychosocial determinants have been proposed, such as the school environment, including demands in school [10] and social support [11]. Furthermore, strained peer and parental relations are associated with elevated levels of psychological distress [12].…”
Section: Introductionmentioning
confidence: 99%
“…This result is parallel with Boulard and colleagues' (2012) study, where being a target of verbal aggression has a clearly stronger association with a depressive mood than poor self-perceived academic achievement. Further, Undheim and Sund (2005) found an association between depressive symptoms and poor teacher support but no connection with depressive symptoms and poor self-perceived academic achievement among 12-yearold girls. More studies on the issue would be required to clarify the connections between school-related characteristics and depressive symptoms.…”
Section: Comparing the Associations Of The School Related Variables Wmentioning
confidence: 72%
“…Feshbach and Feshbach (1987) describe a longitudinal sequence in which depressive symptomology at ages 8 and 9 predicts poorer academic performance two years later, particularly for girls. Undheim and Sund (2005) similarly found that a statistically significant longitudinal relationship between achievement and subsequent depression, only among female participants. Huang's 2015 meta-analysis of 43 studies related to achievement and subsequent depression indicated that biological sex was not a statistically significant moderator of the relationship between achievement and subsequent depression.…”
mentioning
confidence: 78%
“…Previous large-scale longitudinal studies indicate that depression is not correlated with subsequent educational attainment (Breslau et al, 2008;Hanson et al, 2004;Miech et al, 1999;Needham, 2009), while other studies yielded a statistically significant negative effect of adolescent depression on graduation rates and postsecondary education (Fletcher 2008;Needham 2009). Fewer primary studies examined the impact of achievement on subsequent depression, but there is limited evidence that achievement problems predict future depressive symptomology (Feshbach et al, 1987;Huang, 2015;Undheim et al, 2005).…”
Section: The Current Studymentioning
confidence: 99%